O uso do plano de estudo da pedagogia da alternância no ensino e aprendizagem de bioquímica em uma escola pública regular urbana: uma experiência de ensino investigativo a partir da realidade - Capaz, Josieli Parteli (2022)
In urban regular public schools (RPS), the idea of the superiority of scientific content in relation to everyday knowledge still prevails, fragmenting knowledge and subalternizing popular knowledge. As a strategy to overcome this configuration and seeking for the school to act based on the totality of knowledge, so that the lived reality is part of the teaching and learning processes, we seek Teaching by Investigation and the Pedagogy of Alternation as inspiration to promote processes of teaching and learning in Biology contextualized and guided by the exercise of questioning and critical reflection. The understanding, for example, about the biochemistry of food, which was the focus with which we worked, allows students to make more conscious decisions, basing their choices about which foods are important, beneficial and necessary for the maintenance of health. and which ones are harmful, being necessary to avoid them. In addition, the study of biochemistry allows us to understand the effects of food and nutrients on the body. However, the approach to this content is not always in a way that allows this critical awareness to the student, who, as a result, often finds it difficult to understand, which is related to the teaching and learning perspective. adopted in the classroom. Commonly, the approach to content is based on the intense use of expository methods, causing students to not feel motivated or to take ownership of the content. To avoid this, in an urban RPS, we used the Study Plan (SP), a mediation typical of the pedagogy of alternation, used in rural schools, seeking to develop a differentiated didactics in the Biology discipline in a school characterized by traditional pedagogy. In this context, the dissertation presented here has as its research problem the following question: how can the Study Plan for the Pedagogy of Alternation be used in the discipline of Biology in a regular public school and what is its impact on the teaching and learning processes? To answer this question, the study made use of qualitative-quantitative approaches and the action research method, aiming to consolidate, in a pedagogical material, a teaching and learning experience that pointed out the potential of the SP for the teaching of biochemistry in urban RPS's . The production of data took place with a class of the 1st grade of high school located in São Gabriel da Palha, northwest of Espírito Santo, using a combination of techniques. To collect them, we used observation recorded in a logbook, document analysis - the documents, in this case, were reports produced by students during the development of the SP - and application of questionnaires. The analysis of data from structured questions was performed using graphs and took into account the data collected by the set of techniques, promoting their intertwining. The data obtained with the unstructured items, in turn, were, as well as those obtained in observation, subjected to content analysis, as recommended by Bardin (2016). The conclusion obtained is that the Study Plan for the Pedagogy of Alternation presents several possibilities of use outside its original context and that teaching based on the reality of the subjects contextualizes scientific knowledge and drives the teaching and learning processes. Experience has shown that, although different, there is an approximation between SP and research teaching, which leads us to defend the use of this combination in urban RPS's.